DAMPAK PENGGUNAAN BAHASA DAERAH TERHADAP KEMAMPUAN SISWA DALAM MENGUASAI BAHASA INDONESIA DI SDN 3 BAROKO KABUPATEN ENDREKANG - Riswandi Suardi; Muh. Muhsin; Yesi Yupitasari; Fatimah Azzahra; Yunita Eka Putri (Jurnal Risalah Addariyah: Studi Ilmu-Ilmu Keislaman, Pendidikan dan Sosial Kemasyarakatan, 2026)
This study aims to analyze the impact of using local languages on students' proficiency in the Indonesian language at SDN 3 Baroko, Baroko Subdistrict, Enrekang Regency. Using a qualitative case study approach, the research involves students from grades IV, V, and VI, along with teachers and parents. Data were collected through observation and in-depth interviews to explore patterns of local language use and its influence on Indonesian language skills, including reading, writing, speaking, and listening. The findings indicate that using local languages positively impacts students by facilitating understanding during early learning stages, boosting confidence, and strengthening local cultural identity. However, negative effects were also observed, such as difficulties in mastering formal Indonesian terms, which affect academic performance and examination results. Proposed solutions include increasing the intensity of Indonesian language use in schools, training teachers in bilingual teaching strategies, utilizing Indonesian-based learning media, and implementing literacy programs. Collaboration between teachers and parents is also crucial to reinforce Indonesian language skills at home. With a balanced strategy, local language preservation can be achieved without hindering the mastery of Indonesian as the official language of national education.